Testing Of The Nephroprotective Effectiveness Of Sail Leaf (Syzygium Polyanthum (Wight.)Walp.) In DoxorubisinInduced Male Wistar Rat - Dewi; Ali Nafiah Nasution; Ermi Girsang (International Journal of Science, Technology & Management, 2021)
Cancer is one of the leading noncommunicable diseases leading to death worldwide. Cancer treatment has progressed but has side effects including nephrotoxic effects. The toxicity of doksorubisin has been widely known which is likely to be chained by the metabolic conversion of doxorubicin to doxorubicinol. The main mechanism of doxorubicinol toxicity occurs due to its interaction with iron and the formation of ROS that damages cell macromolecules. One of the plants that are widely used by the community to deal with various diseases and prevention is bay leaves. Bay leaves contain secondary metabolites that are antioxidant in nature. Antioxidants are needed to protect the body's cells from oxidative damage, preventing various degenerative diseases such as cancer, cardiovascular disease. The study aimed to determine the content of nephroprotective EEDS chemical compounds in phytochemical screening, EEDS characterization and EEDS nephroprotective activity in doxorubicin-induced mice based on uric acid, ureum and creatine levels. The study was experimentally laboratory using mice as test animals. The treatment group consisted of CMC-Na 0.5%, Nature E, EEDS doses of 100 mg/kgBB, 300 mg/kgBB and 500 mg/kgBB followed by administration of doxorubicin. The results showed phytochemicalally EEDS contains chemical compounds that are nephroprotective namely flavonoids, steroids / triterpenoids, saponins . EEDS has a water soluble sari content value of 21.64%, total ash content of 1.79%, water content of 9.98%. Ethanol soluble juice levels were 45.38% and acid insoluble ash levels were 0.39%. EEDS doses of 100 mg/kgBB, 300 mg/kgBB and 500 mg/kgBB can lower uric acid, ureum and cretinine levels and can picture the histopathology of doxorubicin-induced mouse kidneys with an effective dose of 500 mg/kgBB. It can be concluded that ethanol extract of bay leaves has nephroprotective activity.